Towards a comprehensive understanding of p75 neurotrophin receptor functions and interactions in the brain - Ritala Joel F; Lyne Sean B; Sajanti Antti; Girard Romuald; Koskimäki Janne (Chinese Association of Rehabilitation Medicine, 2022)
The role of neurotrophins in neuronal plasticity has recently become a strong focus in neuroregeneration research field to elucidate the biological mechanisms by which these molecules modulate synapses, modify the response to injury, and alter the adaptation response. Intriguingly, the prior studies highlight the role of p75 neurotrophin receptor (p75NTR) in various injuries and diseases such as central nervous system injuries, Alzheimer's disease and amyotrophic lateral sclerosis. More comprehensive elucidation of the mechanisms, and therapies targeting these molecular signaling networks may allow for neuronal tissue regeneration following an injury. Due to a diverse role of the p75NTR in biology, the body of evidence comprising its biological role is diffusely spread out over numerous fields. This review condenses the main evidence of p75NTR for clinical applications and presents new findings from published literature how data mining approach combined with bioinformatic analyses can be utilized to gain new hypotheses in a molecular and network level.